All Paths Leading to the Library: Youth Mobility and Community-Based Planning. (June 2023) - Sarmiento, Carolina S.; Duarte, Catherine
In the context of a community-based planning process to relocate a neighborhood public library in Madison, Wisconsin, this research examines youth's everyday mobility to improve their access to public space. Through an analysis of field notes, cognitive maps, and interviews with fifth and eighth graders, researchers find that youth move relatively independently every day while using different place-making strategies. The research also finds that mobility options among youth are racialized experiences with important implications in accessing services like the library. The article identifies library planning as an important process for building inclusive community spaces.